Association of lncRNA H19 polymorphisms with cancer susceptibility: An updated meta-analysis based on 53 studies - Yuan, Yingying; Wang, Yachun; Niu, Xiaodong; Han, Yungang; Li, Wenbo; Cheng, Meijin; Li, Zheng; Tan, Jiao; Zhao, Yue; Wang, Wei (Frontiers in Genetics, 2022)
The association between polymorphisms in lncRNA H19 and cancer susceptibility remains to be inconsistent. This study aimed to provide a more precise estimation of the relationship between lncRNA H19 polymorphisms and the risk of cancer based on all available published studies. 53 studies encompassing 32376 cases and 43659 controls were included in our meta-analysis by searching the Pubmed, Embase, Web of Science, WanFang, and CNKI databases. Pooled ORs and their 95% CIs were used to estimate the strength between the SNPs in H19 (rs217727, rs2839698, rs2107425, rs3024270, rs2735971, rs3741216, and rs3741219) and cancer susceptibility. The results showed that H19 rs2839698 polymorphism was associated with increased cancer risk in all participants under three genetic models. However, no significant association was identified between the other six SNPs as well as an overall cancer risk. Stratification by ethnicity showed that rs2839698 mutation indicated to be an important hazardous factor for the Asian population. While rs2107425 mutation had a protective effect on the Caucasian population. Stratification by cancer type identified that rs217727 mutation was linked to increased susceptibility to oral squamous cell carcinoma, lung cancer, and hepatocellular carcinoma; whereas rs2839698 mutation was associated with an elevated risk of hematological tumor and digestive system tumor (p < 0.05). Besides, the rs2735971 mutation was connected with the digestive system tumor. In summary, the rs217727, rs2839698, rs2107425 and rs2735971 polymorphisms in H19 have associations with cancer susceptibility.